Prevalence and leukotoxic profile of biofilm forming Staphylococcal strains isolated from a tertiary care hospital in Mysore - Pradeep Halebeedu Prakash; Shubha Gopal (Tropical Journal of Pathology and Microbiology, 2016)
Background: Staphylococci causes chronic skin infections, device associated infections, ear infections, bone infections and post-operative infections. It secretes toxins such as Pantone-Valentine Leukocidin which prolongs the infection in hospitalized patients.Aim: To investigate the prevalence of Staphylococcal biofilm associated strains and to understand the correlation between biofilm production, multi-drug resistance and leukotoxicity.Methods: 280 Staphylococcal clinical isolates obtained from biofilm associated infections are collected from a tertiary care hospital in Mysore. They were screened for the production of biofilm, multi-drug resistance and leukotoxicity. They were also screened for icaAB and PVL luk F/S genes by PCR. Correlation between leuktoxicity and biofilm production was established by finding the leukotoxic potential of biofilm positive strains.Findings: Among 280 Staphylococcal clinical isolates, 34.6% showed biofilm production. Out of these isolates, 25% showed the presence of icaAB genes and 29% showed the presence of PVL luk F/S genes. Presence of icaAB gene was found to be higher in isolates obtained from implant associated infections. But the prevalence of PVL luk F/S genes was higher in chronic skin infections. 78% of the isolates displayed multi-drug resistance and methicillin resistant strains were comparitively high in device associated infections (77%). Strong biofilm producing PVL positive isolates from chronic skin infections showed increased leucotoxicity compared to PVL negative, weak and moderate biofilm producers.Conclusion: Statistical analysis revealed that PVL in association with biofilms can promote higher leukotoxicity compared to non biofilm producers. This study foresee the essential role of biofilm production, multi-drug resistance and toxins for the increased Staphylococcal pathogenesis.